1999
DOI: 10.3354/meps189125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in community structure in temperate marine reserves

Abstract: ABSTRACT. 'No-take' marine reserves provide a valuable tool for managing marine resources as well as for providing relatively undisturbed habitat with which to assess modifications to ecosystems. We studied 2 marine reserves in northeastern New Zealand, the Leigh Marine Reserve (established 1975) and Tawharanui Marine Park (established 1982) in order to assess whether changes in protected predator populations had resulted in other indirect changes to grazers and consequently to algal abundance. Estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
299
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(317 citation statements)
references
References 30 publications
15
299
2
1
Order By: Relevance
“…taxonomic measurements of diversity suggested sponge flats were more diverse than traditional indices (S, H', l-X, Nl, N2) would otherwise infer. Previous studies have shown that differences in diversity between habitats could be owing to varying levels of structural complexity (Mora et al 2003;Anderson & Millar 2004) and productivity (Taylor 1998;Babcock et al 1999), although these factors were not quantified in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…taxonomic measurements of diversity suggested sponge flats were more diverse than traditional indices (S, H', l-X, Nl, N2) would otherwise infer. Previous studies have shown that differences in diversity between habitats could be owing to varying levels of structural complexity (Mora et al 2003;Anderson & Millar 2004) and productivity (Taylor 1998;Babcock et al 1999), although these factors were not quantified in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…For example Heliocidaris erythrogramma at Maria Island is characteristically cryptic, remaining in crevices or burrows, rarely venturing out to feed, and surviving on drift algae (30). In northeastern New Zealand, the urchin Evechinus chloroticus is often conspicuous at depths between 6-12 m and creates barren grounds by openly grazing on kelp forests (11). However, in reserves Evechinus changes its behavior, becoming cryptic (13) and surviving on drift algae (31), most likely a response to increased densities of predators, as has been experimentally confirmed in other urchins (32).…”
Section: Discussionmentioning
confidence: 99%
“…The few changes observed in populations of nontargeted species in reserves are thought to result from indirect effects that develop after the restoration of populations of higher predators (11)(12)(13)(14). For example, in tropical systems, the recovery of herbivorous fish in reserves can lead to a decrease in macroalgal biomass and the release of space, resulting in enhanced recruitment of corals (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This stems from their relative simplicity, ease of enforcement and intuitive logic. The perceived failures of traditional methods of fisheries management worldwide with declining stocks, overfishing, and general fleet overcapacity (Worm et al 2009, Pauly et al 2002 have also contributed to the clamor for Marine Protected Areas to be set up (Sumaila et al 2000, Kaiser 2005, Laurel and Bradbury 2006, Babcock et al 1999. Furthermore some recent studies have shown that, in comparison with other human maritime activities, (e.g.…”
Section: Introductionmentioning
confidence: 99%